Voices of Resistance: Interdisciplinary approaches to Chican@ children's literature - Herrera, Luz Yadira (Educational (Re)naissance, 2018)
Voices of resistance: Interdisciplinary approaches to Chican@ children's literature gathers a wide range of experts from diverse academic fields in the analysis of Chicanx children’s and young adult (YA) literature. The editors convincingly make the case for the urgency of using multicultural children’s literature as a means for empowerment and social justice. The book provides a solid framework that is useful to multiple audiences–from caregivers, teachers, school leaders, community members, to teacher educators, and beyond. The book highlights the Chicanx history of resistance, as indicated in its title, situated in the various US socio-political contexts that have negatively impacted people of color since the country’s formation. The book reminds us of the important role that literature has on the lives of children; and its potential to either affirm an asset-based perspective connected to their lives, cultural identities, gender constructions, and home language practices of Chicanx children and youth, or to perpetuate harmful deficit views. Furthermore, the book reminds us that powerful children’s and YA literature can help raise Chicanx children’s consciousness, even from a young age, towards sustaining self-love in the uplifting of Chicanx identity, culture, and linguistic practices. (Rowman & Littlefield, 2018)